2015
DOI: 10.1002/jmv.24395
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of HIV‐1 reverse transcriptase at baseline and time of failure in patients receiving rilpivirine in the phase III studies ECHO and THRIVE

Abstract: Minority variants (1.0-25.0%) were evaluated by deep sequencing (DS) at baseline and virological failure (VF) in a selection of antiretroviral treatment-naïve, HIV-1-infected patients from the rilpivirine ECHO/THRIVE phase III studies. Linkage between frequently emerging resistance-associated mutations (RAMs) was determined. DS (llIumina®) and population sequencing (PS) results were available at baseline for 47 VFs and time of failure for 48 VFs; and at baseline for 49 responders matched for baseline character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The DRMs detected by MiSeq and Sanger sequencing were in complete (100%) agreement for those representing more than 20% of the virus quasispecies, which agreed with the findings of previous studies . Plasma samples from patients with primary HIV‐1 infections had higher virus loads than samples from patients who failed antiretroviral treatment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The DRMs detected by MiSeq and Sanger sequencing were in complete (100%) agreement for those representing more than 20% of the virus quasispecies, which agreed with the findings of previous studies . Plasma samples from patients with primary HIV‐1 infections had higher virus loads than samples from patients who failed antiretroviral treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Minority DRMs should be more easily detected in high virus‐load samples as they are present in greater absolute quantities with the limitation of a quasispecies more homogeneous in primary infection. As expected, MiSeq sequencing identified minor mutations not observed by Sanger sequencing because they accounted for less than 20% of the quasispecies . Some DRMs were detected only by one or other of the MiSeq and 454 GS‐FLX sequencing methods; they generally accounted for a small percentage of the virus quasispecies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Some analyses have shown that low-frequency drug resistance mutations (DRMs), especially those conferring resistance to non-nucleoside reverse transcriptase inhibitors (NNRTIs), are associated with virological failure after initiating combination ART-containing NNRTIs (3)(4)(5)(6)(7)(8)(9)(10)(11). In contrast, other studies have found no association with treatment outcomes when low-frequency resistance mutations are detected that confer resistance to an ARV drug used in the regimen (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These conflicting results make interpretation of resistance results from newer, more sensitive resistance assays difficult (30).…”
Section: Introductionmentioning
confidence: 99%